In-vivo evaluation of analgesic and anti-inflammatory activities of the 80% methanol extract of Acacia seyal stem bark in rodent models - Gena Kedir; Akeberegn Gorems Ayele; Workineh Shibeshi (BMC, 2024)
Abstract Background Pain and inflammation are the major medical condition commonly addressed with traditional remedies. Acacia seyal is a traditional herb widely used in Ethiopian folk medicine for pain management. However, its effectiveness has yet to be validated through scientific or experimental research. Therefore, the current study aims at evaluating the in vivo analgesic and anti-inflammatory effects of 80% methanolic stem bark extract of Acacia seyal in rodent models. Methods After successful extractions of the stem barks of Acacia seyal with 80% methanol, the pain relieving effects of 100, 200 and 400 mg/kg extract were evaluated using acetic acid-induced writhing test and hot plate method whereas the anti-inflammatory profile was determined by carrageenan induced paw-edema model and cotton pellet induced granuloma technique. Results The 80% methanol Acacia seyal stem bark extract exhibited substantial (p < 0.001) analgesic effect in acetic acid induced writing test (p < 0.001). The plant extract also witnessed significant central analgesic effect in hot plate method beginning at 30 min with maximum % elongation time occurred at 120 min. Furthermore, the acacia stem bark extract produced anti-inflammatory effect against carrageenan induced paw-edema model. In cotton pellet induced granuloma model, the 200 and 400 mg/kg doses of the current plant material appeared to inhibit granuloma mass formation and exudate reduction significantly (p < 0.001). Conclusion The collective findings of the current study revealed that 80% methanol extracts of Acacia seyal exhibited considerable analgesic and anti-inflammatory activities, supporting the plant's traditional use for management of pain and inflammatory disorders.